Conscientiousness, openness to experience and extraversion as predictors of nursing work performance: a facet‐level analysis. (3rd May 2015) - Ellershaw, Julia; Fullarton, Christie; Rodwell, John; Mcwilliams, John
Abstract : Aim: This study examined the relationships between the personality traits of conscientiousness, openness and extraversion at trait and facet‐levels and three indicators of work role performance; proficiency, 'adaptivity' and proactivity measured at individual, team and organisational levels. Background: This is one of the first studies to explore the relationship between personality, measured at trait and facet‐level and performance using a comprehensive range of performance indicators. Method: An online survey of 393 nurses from health‐care organisations across Australia was conducted to test hypothesised relationships. Results: Path analyses revealed numerous relationships between personality, measured at both trait and facet‐levels, and work role performance. Conscientiousness was highlighted as the strongest driver of work role performance across all the indicators, with extraversion also strongly associated with work role performance. Openness to experience, previously considered a week predictor of performance, was, when examined at the facet‐level, related to all of the work role performance indicators. Conclusions: Results suggests a bandwidth effect, where the personality traits drive global performance while the facets drive specific performance. Implications for nursing management: Better understanding of the relationship between personality and work role performance will help nurse managers to foster the fit between individual and organisation, improving job satisfaction, engagement, retention and performance in role.